Knowledge about osteoporosis prevention among women screened by bone densitometry - Janiszewska, Mariola; Firlej, Ewelina; Żołnierczuk-Kieliszek, Dorota; Dziedzic, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction : Osteoporosis is an illness characterized by the handicapped endurance of the bones, causing an increased risk of fracture. Aim of the study was to establish the level of knowledge about osteoporosis prevention among women screened by bone densitometry and to answer the question whether the level of knowledge is dependent on socio-demographic factors. Material and methods: The research was realized by means of a survey method, a poll technique in 2014. The study involved 292 women aged 51-83. The examined women were patients undergoing bone densitometry in the healthcare centres in Lublin. The osteoporosis knowledge test (OKT, revised 2011) by Phyllis Gendler was used as a research tool. Gathered material was subject to descriptive and statistical analysis. Tukey’s test, t-Student test and variance analysis (ANOVA) were all applied. A statistical significance level was set at  = 0.05. Results and conclusions : Respondents presented the basic exercise knowledge (M = 9.97) and low knowledge concerning risk factors, screening and treatment of osteoporosis (M = 7.87). The calcium knowledge remained on an average level (M = 14.03). Better educated women, city inhabitants as well as women having very good or good social and welfare conditions showed a significantly higher level of knowledge about osteoporosis prevention. Even women undergoing bone densitometry examination present insufficient knowledge about osteoporosis prevention.